Guest Editors: Counseling Psychology, Drug Prevention and Rehabilitation Issues - Dini Farhana Baharudin; Mohd Rosmizi Abd Rahman; Siti Nubailah Mohd Yusof; Nurhafizah Mohd. Sukor; Haslee Sharil Lim Abdullah (Universiti Sains Islam Malaysia, 2024)
This special issue is a selection of seven articles that are research-based. The articles were extracted from the Master of Counseling (Substance Abuse), Universiti Sains Islam Malaysia students' research reports. The students were assisted by their respective supervisors to produce the articles as a form of academic training to disseminate their research findings through journal publication.